[4π+2π] Cycloaddition Between a D-Erythrose Imine and Different Nucleophilic Dienes - Ferreira, Juliana Patrícia Moreira Marques (2015)
Imino-Diels–Alder reaction has been known for many years, but only recently major advances have been made, specially through the development of catalytic asymmetric synthesis.1 It have been proved however that under acid catalysis [4π+2π] processes are not concerted, but otherwise ionic,2 Nevertheless the selectivity may be maintained, as occurred in the present work. Simple nucleophilic dienophiles react with D-erythrose N-arylimine 1 to give single products, due to the facial selectivity interaction of reagents. Nucleophic dienes, such as the example shown in Scheme 1 acted both as diene in a formal “inverse electron-demand” Diels-Alder reaction, and as “normal electron-demand” reaction. The results obtained will be discussed.